(untitled) (The Review of Diabetic Studies, 2017)
BACKGROUND: The incidence of type 1 diabetes (T1D) is rising, which might be due to the influence of environmental factors. Biological and epidemiological evidence has shown that excess iron is associated with beta-cell damage and impaired insulin secretion. AIM: In this review, our aim was to assess the association between iron and the risk of T1D. METHODS: A systematic literature search was performed in PubMed and EMBASE in July 2016. Studies investigating the effect of iron status/intake on the risk of developing T1D later were included, and study quality was evaluated. The results have been summarized in narrative form. RESULTS: From a total of 931 studies screened, we included 4 observational studies evaluating iron intake from drinking water or food during early life and the risk of T1D. The quality of the studies was moderate to high assessed via the nine-star Newcastle Ottawa Scale. One out of the four studies included in this review found estimates of dietary iron intake to be associated with risk of T1D development, whereas three studies found no such relationship for estimates of iron in drinking water. CONCLUSIONS: The limited number of studies included found dietary iron, but not iron in drinking water, to be associated with risk of T1D. Further studies are needed to clarify the association between iron and risk of T1D, especially studies including measurements of body iron status.